(untitled) (SCIENCE TIME JOURNAL, 2026)
This research represents students` motivation as a critical factor in language learning success, influencing the effort learners invest, their persistence in the face of challenges, and ultimately their achievement of proficiency. Understanding how AI integration affects motivation is therefore essential for evaluating the pedagogical value of these technologies. This study provides particularly valuable empirical evidence on this relationship, demonstrating that AI-enhanced instruction can significantly enhance multiple dimensions of learner motivation. For educational institutions and policymakers, the findings underscore the importance of investing in technological infrastructure to ensure equitable access, providing comprehensive professional development for teachers on AI integration, developing ethical frameworks and policies for AI use in education, and supporting research on effective practices for AI-enhanced language learning. The rapid evolution of AI technologies requires that institutions remain adaptive and responsive, continuously evaluating and refining their approaches as new capabilities and challenges emerge.